Macro Nutrient Content Of Combined Vermicompost Fertilizer And Tofu Drainage Waste Using Lumbricus Rubellus Worm - Marselinus Banu; Josua Sahala; Wolfhardhus Vinansius Feka; Jefrianus Neonnub; Agustinus Agung Dethan; Ernanda Sofi; Maria Selfiana Pasi; Maria Magdalena Kapitan; Maria Metriana Seran (Poltanesa, 2026)
This research was conducted to identify the macro-nutrient levels contained in vermicompost produced from a combination of Bio-slurry and tofu waste processed with Lumbricus rubellus. The study applied a single-factor experimental design focusing on the proportion of Bio-slurry mixed with tofu dregs, which served as an additional energy supply for the worms during vermicomposting. The experiment was carried out from June to July 2025 at the Animal Husbandry Laboratory, Faculty of Agriculture, Science, and Health, Timor University, Sasi Village, Kefamenanu. A Completely Randomized Design (CRD) consisting of four treatments and four replications was used, totaling 16 experimental units. The treatments included: P0 = 5 kg Bio-slurry + 250 g worms; P1 = 5 kg Bio-slurry + 200 g tofu dregs + 250 g worms; P2 = 5 kg Bio-slurry + 400 g tofu dregs + 250 g worms; and P3 = 5 kg Bio-slurry + 600 g tofu dregs + 250 g worms. The results revealed significant differences (P < 0.05) in Nitrogen, Phosphorus, and Potassium contents. Treatment P3 showed the highest levels of Nitrogen (2.15%), Phosphorus (0.95%), and Potassium (0.93%). Based on these findings, adding 600 g of tofu dregs produced the most optimal macro-nutrient composition in the resulting vermicompost.